Person references, change in footing, and agency positioning in psychotherapeutic conversations - Wahlström, Jarl (Frontiers in Psychology, 2023)
This study investigated how clients and therapists, when discussing the client’s difficulties, made use of two specific conversational practices, that is, different grammatical forms of person reference and changes of footing, and what the consequences of this was for how the clients were positioned in relation to their problematic experiences. A data corpus of the first sessions of nine psychotherapies at a university training clinic in Finland was utilized. The uses of person references and changes of footing in therapists’ initiative turns, clients’ responses, and therapists’ third position (recipient) actions were examined. The analysis showed that in initiative turns therapists usually used second person singular, as an invitation for the client to respond from his/her personal point of view, and thus ascribing active agency to the client. When telling their problematic experiences clients typically used so called zero person constructions, presenting such experiences as common to people in general, and thus lessening their agency and inviting the therapist to share their experiential position. In recipient actions, therapists could use a combination of zero and active person reference which served to communicate an empathic stance and an invitation to the client to take an agentic observer position. Almost exclusively only therapists used changes of footing. This could happen rapidly within single utterances and served to express affiliation with the client’s emotional experience and to invite or challenge the client to take an observer position.